Switching impulse discharge characteristics of UHV transmission line air gaps. Issue 5 (9th January 2019) - Gao, Jiachen; Wang, Linong; Zhang, Qiushi; Song, Bin; Liu, Kai; Xiao, Bin
Abstract : The design of external insulation for transmission lines is usually based on real‐type experiments. With the increasing voltage level of the transmission lines, in order to better design the experiments and reduce the experiment workload in the future, this paper studies the switching impulse discharge characteristics of air gaps of an ultrahigh‐voltage (UHV) transmission line. A long air gap switching impulse breakdown voltage prediction method based on the leader discharge mechanism is proposed in this paper, and a continuous leader inception model is fitted for the air gaps in UHV transmission lines by calculating the factor R of the conductor–plane gaps. The method and the model can effectively predict the air gap breakdown voltage of transmission lines. The influence of tower width and conductor structure on air gap breakdown characteristics of UHV transmission lines is studied by the method and the model proposed this paper. The results show that, as the width of the tower increases, the breakdown voltage decreases, and as the gap length increases, the influence of the tower width on the breakdown voltage decreases. The conductor structure has no obvious influence on the discharge characteristics of transmission line air gaps. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.